Adherence to and determinants of guideline‐recommended biomarker testing and targeted therapy in patients with gastroesophageal adenocarcinoma: Insights from routine practice. Issue 14 (17th March 2021) - Lau‐Min, Kelsey S.; Li, Yimei; Eads, Jennifer R.; Wang, Xiaoliang; Meropol, Neal J.; Mamtani, Ronac; Getz, Kelly D.
Abstract : BACKGROUND: Anti human epidermal growth factor receptor 2 (anti‐HER2) therapy with trastuzumab improves overall survival in patients with advanced, HER2‐positive gastroesophageal adenocarcinoma (GEA) and is now incorporated into national guidelines. However, little is known about adherence to and determinants of timely HER2 testing and trastuzumab initiation in routine practice. METHODS: The authors performed a cross‐sectional study of patients who had advanced GEA diagnosed between January 2011 and June 2019 in a nationwide electronic health record‐derived database. The annual prevalences of both timely HER2 testing (defined within 21 days after advanced diagnosis) and timely trastuzumab initiation (defined within 14 days after a positive HER2 result) were calculated. Log‐binomial regressions estimated adjusted prevalence ratios comparing timely HER2 testing and trastuzumab initiation by patient and tumor characteristics. RESULTS: In total, the cohort included 6032 patients with advanced GEA of whom 1007 were HER2‐positive. Between 2011 and 2019, timely HER2 testing increased from 22.4% to 44.5%, whereas timely trastuzumab initiation remained stable at 16.3%. No appreciable differences in timely testing or trastuzumab initiation were noted by age, sex, race, or insurance status. Compared with patients who had metastatic disease at diagnosis, patients who had early stage GEA who did not undergo surgery were less likely to receive timely HER2 testing and trastuzumab initiation (testing prevalence ratio, 0.69; 95% CI, 0.64‐0.75; treatment prevalence ratio, 0.32; 95% CI, 0.18‐0.56), as were patients with early stage disease who subsequently developed a distant recurrence (testing prevalence ratio, 0.56; 95% CI, 0.47‐0.65; treatment prevalence ratio, 0.61; 95% CI, 0.24‐1.55). CONCLUSIONS: In patients with advanced GEA, guideline‐recommended HER2 testing and anti‐HER2 therapy remain underused. Uptake may improve with universal HER2 testing regardless of stage. Abstract : Timely HER2 biomarker testing and targeted therapy administration remain in use for patients with advanced gastroesophageal adenocarcinoma. Compared with patients initially diagnosed with de novo metastatic disease, those diagnosed with early stage disease who develop a recurrence or who do not undergo curative surgery are less likely to receive timely precision oncology care.